Perancangan Iklan Explainer Video Monumen Kapal Selam dengan Teknik Animasi 2D untuk Menumbuhkan Kesadaran Terhadap Sejarah Surabaya - Ansori, Agung Gumelar; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
The purpose of designing ads Submarine Monument explainer video with 2D animation techniques to introduce Submarine Monument and develop awareness of the history of Surabaya. Design explainer video ads using qualitative data collection methods, namely by interview, observation, documentation studies, existing studies and literature studies are very important for determining the design concept of the study. From the analysis of these data, the theme of the design concept derived is great. The concept of